Renal Responses to Chronic Suppression of Central Sympathetic Outflow - Iliescu, Radu (2012)
Chronic electrical activation of the carotid baroreflex produces sustained reductions in sympathetic activity and arterial pressure and is currently being evaluated as hypertension therapy for patients with resistant hypertension. However, the chronic changes in renal function associated with natural suppression of sympathetic activity are largely unknown. In normotensive dogs we investigated the integrative cardiovascular effects of chronic baroreflex activation (2 weeks) alone and in combination with the calcium channel blocker amlodipine, which is commonly used in the treatment of resistant hypertension. During baroreflex activation alone, there were sustained decreases in mean arterial pressure (17 ± 1 mm Hg) and plasma [norepinephrine] (NE, ~35%), with no change in plasma renin activity (PRA). Despite low pressure, sodium balance was achieved due to decreased tubular reabsorption, because GFR and renal blood flow decreased 10–20%. After 2 weeks of amlodipine, arterial pressure was also reduced 17 mm Hg, but with substantial increases in NE and PRA, and no change in GFR. In the presence of amlodipine, baroreflex activation greatly attenuated neurohormonal activation and pressure decreased even further (by 11 ± 2 mm Hg). Moreover, during amlodipine administration the fall in GFR with baroreflex activation was abolished. These findings suggest that the chronic blood pressure lowering effects of baroreflex activation are due, at least in part, to sustained inhibition of renal sympathetic nerve activity and attendant decreases in sodium reabsorption prior to the macula densa. Tubuloglomerular feedback constriction of the afferent arterioles may account for reduced GFR, a response abolished by amlodipine, which dilates the preglomerular vasculature.